ANALISA PEMBERIAN DOSIS PUPUK KASCING DAN MACAM ASAP CAIR TERHADAP PENINGKATAN PRODUKSI TANAMAN TOMAT (Solanum lycopersicium L.) - Mariyatul Qibtiyah; Sya’adah Sya’adah; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Tomato (Solanum lycopersicium L.) is a seasonal fruit that is widely concumed fresh. The aim of this research is to determine the effect of using vermicompost fertilizer and liquid smoke on increasing tomato production. This research was carried out from February to May 2023 in Karangwungulor Laren Lamongan. This study used a factorial randomized block design (RAK) involving two factors with three levels of each factor. Which consists of vermicompost fertilizer dosage factors: no vermicompost fertilizer, 8 t/ha vermicompost fertilizer, 10 t/ha vermicompost fertilizer as well as liquid smoke type factors: no liquid smoke, rice husk liquid smoke, coconut shell liquid smoke. Fisher’s test (F test) was used to analyze differences in data collected from these observations, with a significance level of 5% and 1%. The least significant difference test is applied at a significance level of 5% to further analyze treatments that have a real impact. Specifically, the observed parameters showed that there was an interaction between the treatmen dose of vermicompost fertilizer and the type of liquid smoke on the parameters of plant height at 21 days after olanting, number of branches at 28 days after planting, and number of fruit at 49 days after planting. There was a very significant difference in the height parameters of plant aged 28 days after planting and 35 days after planting. Number of leaves aged 14 days after planting, 21 days after planting, 28 days after planting, and 35 days after planting. Number of flowers aged 35 days after planting, 42 days after planting, and 49 days after planting. Number of fruit aged 35 days after planting, 42 days after planting, and 56 days after planting. Fruit diameter. Fruit weight per plot. Fruit weight per hectare. The treatment of 8 t/ha vermicompost fertilizer and rice husk liquid smoke gave better results compared to other treatments.